Spatio-temporal variation of surface water quality and pollution source apportionment using environmetrics in Jakara Basin, Nigeria - Mustapha, Adamu (2013)
Spatio-temporal variation of surface water quality and identification of water pollution sources in a river basin are very important and critical element in the assessment of water resources protection and sustainable utilization. In this study,various environmetric tools including principal component analysis (PCA), factor analysis (FA), hierarchical agglomerative cluster analysis (HACA), discriminate analysis (DA), multiple linear regression, structural equation modelling (SEM), analysis of variance (ANOVA), paired sample t-test and Pearson product moment correlation coefficients were used to evaluate the spatio-temporal variation and pollution sources of Jakara Basin, north-western Nigeria. Surface water in the Jakara basin was collected in four phases: preliminary sampling, dry and wet sampling, Getsi River sampling and three other tributaries. PCA and FA were used to investigate the origin of water quality parameters. Seven principal components were obtained with explained 77% total variation of water quality. Hierarchical cluster analysis grouped thirty sampling sites into three clusters based on similarities of river water quality. The results showed that spatially the Basin can be grouped into three statistically significant potential pollution sources (domestic, industrial and agricultural). Temporal water quality variation was investigated using dry and wet seasons water samples. DA revealed five statistically significant parameters for dry season and six parameters for wet season affording more than 77% and 82% respectively. The results showed that temporal water quality in the basin varied with significant differences (p <0.05). The sources of pollution in the area revealed anthropogenic origin have profound influence in the dry season and natural pollution sources have little impact especially during wet season. Significant monotonous trend directions and magnitude of change in the basin in organic compound were detected by trend analysis using Mann-Kendall and Sen Slope estimates confirming anthropogenic influences. Further, a time series Landsat satellite images of 1987, 1995 and 2006 were used to extract land use changes over the past twenty years. Results indicated that there has been a noticeable and uneven urban growth and tremendous loss of cultivated cover. Overall results obtained are potentially useful to assist policy makers to understand the complex nature of the water quality issues and to determine priorities to improve the water quality in the basin.